Pipe Cleaner Flowers Pot - Yeny Novita Fitriani; Danendra Bramantyo; Mohammad Masrur Mauridhoh; Muhammad Yasin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to determine the influence of digital marketing and brand awareness on consumer purchase intention toward the Subeng Klasik product. A quantitative approach was employed using a questionnaire distributed to respondents. The data were analyzed using multiple linear regression. The results indicate that both digital marketing and brand awareness have a positive and significant effect on purchase intention when tested partially. However, brand awareness exerts a greater influence than digital marketing. Simultaneously, both variables also significantly and positively affect purchase intention. These findings imply that strengthening brand awareness strategies should be a primary focus in developing local product marketing such as Subeng Klasik.